2015
DOI: 10.3390/jdb3040112
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor (PEDF) is a Determinant of Stem Cell Fate: Lessons from an Ultra-Rare Disease

Abstract: PEDF is a secreted glycoprotein that is widely expressed by multiple organs. Numerous functional contributions have been attributed to PEDF with antiangiogenic, antitumor, anti-inflammatory, and neurotrophic properties among the most prominent. The discovery that null mutations in the PEDF gene results in Osteogenesis Imperfecta Type VI, a rare autosomal recessive bone disease characterized by multiple fractures, highlights a critical developmental function for this protein. This ultra-rare orphan disease has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 98 publications
(141 reference statements)
0
9
0
Order By: Relevance
“…PEDF was first identified as a 50 kDa secreted protein in conditioned medium from cultured fetal human retinal pigment epithelium (RPE) cells , and was recognized as a potent inhibitor of vascular endothelial growth factor (VEGF) . Recently, PEDF was proposed to regulate the proliferation and differentiation of human embryonic stem cells as well as multiple tissue‐specific stem cells , and was also found in developing and mature human cornea . With regard to hLESCs, it has been reported that the PEDF has the capacity to promote self‐renewal and that such effect may be associated with the p63 expression .…”
Section: Discussionmentioning
confidence: 99%
“…PEDF was first identified as a 50 kDa secreted protein in conditioned medium from cultured fetal human retinal pigment epithelium (RPE) cells , and was recognized as a potent inhibitor of vascular endothelial growth factor (VEGF) . Recently, PEDF was proposed to regulate the proliferation and differentiation of human embryonic stem cells as well as multiple tissue‐specific stem cells , and was also found in developing and mature human cornea . With regard to hLESCs, it has been reported that the PEDF has the capacity to promote self‐renewal and that such effect may be associated with the p63 expression .…”
Section: Discussionmentioning
confidence: 99%
“…PEDF is a secreted factor with multiple biological functions. It was initially considered to be a neurotrophic factor, but its recognized functions later expanded to include a stem cell niche factor, an inhibitor of cancer cell growth and, notably, the most potent natural antiangiogenic factor ( 34 36 ). A number of animal models have demonstrated the therapeutic value of PEDF in the treatment of blinding diseases and multiple types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PEDF has been originally identified in the retina, however, it has now become evident that it is expressed throughout the human body and is constantly present in the systemic circulation [4,5]. Studies in the past years have implicated PEDF in the pathophysiology of a wide range of angiogenesis-associated disorders, including diabetic complications [6,7], macular degeneration [8,9], Osteogenesis Imperfecta Type VI [10,11], and the growth of many types of solid tumors [12][13][14][15][16]. Some of these roles may be mediated by the effect of PEDF on stem cells as was shown in the brain, muscle, and eye [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the past years have implicated PEDF in the pathophysiology of a wide range of angiogenesis-associated disorders, including diabetic complications [6,7], macular degeneration [8,9], Osteogenesis Imperfecta Type VI [10,11], and the growth of many types of solid tumors [12][13][14][15][16]. Some of these roles may be mediated by the effect of PEDF on stem cells as was shown in the brain, muscle, and eye [11]. Furthermore, the natural antiangiogenic activity of PEDF, which is far greater than that of any other known endogenously produced factor [2,17], has turned it into a highly potent therapeutic agent for the inhibition of pathological neovascularization and, therefore, a promising tumor suppressor [18].…”
Section: Introductionmentioning
confidence: 99%